Evaluation of a dead-end ultrafiltration membrane for the removal of organic matter from a water reservoir in Colombia (2016)
ABSTRACT: The removal of natural organic matter (NOM) from surface water sources was evaluated by a pilot ultrafiltration plant through 3 different treatment processes: UF, PAC/UF and PAC/C-S/UF. For UF, the ultrafiltration plant was used as the only treatment. For PAC/UF, tests were performed with powdered activated carbon (PAC) as pre-treatment to the ultrafiltration membrane. For the PAC/C-S/UF hybrid treatment process, adsorption with PAC and coagulation- sedimentation with aluminum sulphate as a coagulant was used as pre-treatment. The results indicated that the best hybrid treatment process was PAC/C-S/UF, since it maintained a stable transmembrane pressure (TMP) of around 0.5 bar in the operating time, while in the this process the flow remained constant at about 227 L / (m2 · h). In addition, with this process, the highest removal efficiencies were obtained for the NOM parameters evaluated. Coagulation pre-treatment improved the removal of NOM in comparison with PAC and UF as the only treatment. The results showed that both hydrophobic and hydrophilic organic compounds could be removed by the action of the coagulant. When further comparing the increased removal rates of the hydrophobic material (HoM) and hydrophilic material (HiM) fractions, it was observed that the hydrophobic organic chromophores could be removed by coagulation more easily than the hydrophilic organic chromophore compounds. The molecular weight distribution (MWD) was evaluated, indicating that the PAC/C-S/UF treatment successfully removed medium-high molecular weight (MW) compounds (> 1701 Da), but the removal efficiency of medium-low MW compounds (≤ 1701 Da) began to decrease as the compounds had lower MW.